N-terminal probrain natriuretic peptide sebagai petanda adanya hipertrofi ventrikel kiri pada pasien hipertensi dibandingkan left ventricle mass index pada ekokardiografi - Mohammad Ariful Munir; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2010)
Background: Some research reports the usefulness of the N-terminal proBrain natriuretic peptide (NT proBNP) as a diagnostic tool for left ven-tricular hypertrophy due to increased levels of NT proBNP in hypertensive patients with left ventricular hypertrophy.Objective:To determine the role of NT pro-BNP in terms of diagnostic tool in hypertensive patients with left ventricular hypertrophy, knowing the value of sensitivity, specificity, positive predictive value, negative predictive value of NT proBNP and levels of NT proBNP in hypertensive patients with left ventricular hypertrophy.Methods: Cross sectional observational study conducted in outpatient clinic RSSA Malang from July 2008 until December 2008. This study mea-sures the level of NT proBNP and echocardiography examinations on 79 hypertensive patients. Pearson correlation test was used to analyze the correlation between NT proBNP with left ventricle mass index(LVMI). Chisquare test was used to determine the value of sensitivity, specificity, positive predictive value, negative predictive value NT proBNP compared with echocardiography. All calculations using a= 5%, 95% confidence intervals and considered significant if p <0.05.Results: The level of NT proBNP left ventricular hypertrophy group were significantly higher than non-left ventricular hypertrophy (797,31±546,08 v 56,09±29,81 pg/ml). There is significant positive correlation between LVMI with NT proBNP (p=0.006, r=0.306). NT proBNP had a sensitivity of 60%, specificity 65.5%, 75% positive predictive value, negative predic-tive value 48.7% and AUC (area under curve) of 0.649. Conclusion: The level of NT proBNP increased in hypertensive patients with left ventricular hypertrophy and there is significant positive correlation between LVMI with NT proBNP. NT proBNP less sensitive and specific than echocardiography to determine left ventricular hypertrophy.